Enhanced sputter yields of ion irradiated Au nano particles: energy and size dependence - Holland-Moritz, Henry; Scheeler, Sebastian; Stanglmair, Christoph; Pacholski, Claudia; Ronning, Carsten (Nanotechnology, 2015)
Hexagonally arranged Au nanoparticles exhibiting a broad Gaussian-shaped size distribution ranging from 30 nm to 80 nm were deposited on Si substrates and irradiated with Ar+ and Ga+ ions with various energies from 20 to 350 keV and 1 to 30 keV, respectively. The size and energy dependence of the sputter yield were measured using high-resolution scanning electron microscopy image analysis. These results were compared to simulation results obtained by iradina, a Monte Carlo code, which takes the specifics of the nano geometry into account. The experimental sputter yields are significantly higher than simulated sputter yields for both bulk and the nano geometry. The difference can be clearly attributed to thermally driven effects, which significantly increase the measured sputter yields.
Gesehen am 07.09.2020